Hexagonal ring microstrip patch antennas for PCS and S-band radar applications - Cihan DOGUSGEN ERBAS (International Journal of Applied Methods in Electronics and Computers, 2020)
In this study, two hexagonal ring microstrip patch antennas for Personal Communication Service (PCS/1850-1990 MHz) and S-band (2000-4000 MHz) radar applications are proposed and simulation results for antenna performance parameters are presented. The antennas consist of a hexagonal ring patch, a ground plane and a dielectric substrate in between. Edge length of each square antenna is 25 mm. Substrate height is 4.3 mm. Relative permittivity and loss tangent of the substrate material are 15.5 and 0.0001, respectively. Distance from center of the antennas to inner and outer hexagon corners are 4 mm and 10.19 mm, respectively. The antennas are fed by a 50-ohm coaxial probe. Depending on the feed location, resonant frequency and therefore application choice is achieved. Center of the antennas is denoted as (0, 0) mm. For the feed location of (-1.50, -4.19) mm, the antenna for PCS application resonates between 1830-2035 MHz with a bandwidth of 205 MHz. Voltage Standing Wave Ratio (VSWR) value at 1900 MHz is 1.1097. Unidirectional radiation patterns are obtained for both Ø=0ᴼ and Ø=90ᴼ planes. Maximum radiations occur at boresight with radiation levels of 12.09 dB and 12.10 dB for Ø=0ᴼ and Ø=90ᴼ planes, respectively. Maximum gain is 3.26 dBi for Ø=0ᴼ plane and 3.09 dBi for Ø=90ᴼ plane. For the feed location of (-7.36, 0.95) mm, the antenna for S-band application resonates between 3280-4015 MHz covering S-band with a bandwidth of 735 MHz. The frequency range and bandwidth are suitable for the radar application. VSWR value at the resonant frequency of 3650 MHz is 1.0164. Again, unidirectional radiation patterns are obtained for both Ø=0ᴼ and Ø=90ᴼ planes. Maximum radiations occur at boresight with radiation levels of 5.82 dB and 5.75 dB for Ø=0ᴼ and Ø=90ᴼ planes, respectively. Maximum gain is 4.14 dBi for Ø=0ᴼ plane and 4.03 dBi for Ø=90ᴼ plane.